Mapletree Real Estate Programme established at SMU through S$3 million endowed gift; SMU to offer specialisation in real estate investment and finance from August 2018 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
Mapletree Investments (“Mapletree”) and Singapore Management University (“SMU”) are pleased to jointly announce the launch of a multi-faceted Mapletree Real Estate Programme (“Programme”). The Programme, which is a first of its kind, aims to equip students with the necessary knowledge and cross-disciplinary skills to navigate the growing real estate sector in Singapore and globally. The Mapletree Real Estate Programme has been made possible by a generous endowed gift of S$3 million from Mapletree to SMU. With a 1:1 government matching, the total sum of S$6 million will go towards the establishment of the Mapletree Professorship in Real Estate, Mapletree Awards, Mapletree Real Estate Business Study Trip Grant, as well as Mapletree Speaker Events.